Xerostomia dan Hiposalivasi pada Pasien Lansia di Rumah Sakit Gigi dan Mulut Universitas Andalas - Gunawan Gunawan; Desy Purnama Sari; Ivony Fitria (Faculty of Dentistry Universitas Andalas, 2023)
The number of elderly people in the world continues to increase annually, including in Indonesia. Over more than a decade(2010–2021), the percentage of the elderly has climbed by at least 3%, reaching 10.82 %. Age-related conditions that negatively affect the physical and mental well-being of the elderly, such as xerostomia and hyposalivation, can lead to a decline in oral function Purpose:This study aims to determine the condition of xerostomia and hyposalivation in elderly patients at the Andalas University Dental and Oral Hospital (RSGM UNAND). Methods:This study usedcross-sectional design, using a total sampling technique involving 35 elderly patients with full edentulous conditions who came to UNAND General Hospital within 3 months. Xerostomiais carried out using a questionnaire that has been tested for its validity and rehabilitation, then salivary flow rate are carried out using the unstimulated saliva collection method to determine the condition of hyposalivation The data was analyzed by computerized by usingspearman test to analyze the relationship between the condition of xerostomiaand hyposalivationang sociodemographic aspects.Results:41.4%of patients had hyposalivation, thus xerostomia affected all patients (62.9% exhibiting low and 37.1% highcomplaint). Theaverage saliva flow rate was 0.51±0.303, and there was no correlation between saliva flow rate and sociodemographic aspects. (p>0.05).Conclusion:Some elderly patients with full edentulous conditions experience hyposalivation and xerostomia conditions caused by lack of salivary production due to aging factors